025 PP: "A FRESH SET OF EYES?" NEGOTIATING THE REALITIES OF EMBEDDED RESEARCH IN PUBLIC HEALTH. (3rd March 2017) - Cheetham, M; Wiseman, A; Gibson, E; Khazaeli, B; Graaf, P Van der; Rushmer, R
Abstract : In collaboration with Fuse, the Centre for Translational Research in Public Health, a local authority public health department in North East England appointed an embedded researcher as part of a new, innovative approach to increasing research evidence in public health. There were two parts to the researcher's role: one to undertake a qualitative evaluation of an 'integrated wellbeing model', a preventive, asset-based approach that supports individuals, families and communities to improve their health and wellbeing. The other was to support the use of research evidence in public health more widely. The researcher was based with the public health team 3 days a week for a year until July 2016. This paper explores the reality of this methodological approach in the field of public health, drawing on the perspectives of the host organisation and the embedded researcher. We describe the assumptions underpinning the approach, how collaborative relationships were established, and what they meant. We reflect on the ways in which this research design, data interpretation and reporting were affected. Examples are used to highlight the challenges and opportunities of a University and Local Authority collaborating in this way. We review what we have learned about collaboration, with a view to sharing transferable messages. The aim is to explore the effectiveness of embedded research, and prompt debate about the pros and cons of collaborating in this way, drawing on our experiences.